Fetal Acardia Syndrome in monozygotic twin pregnancy: Case report - Carvalho, Cristopher Mateus; Freire, Sara Iasmim Santos; Maia , Maria Luiza Peloso; Freitas, João Manoel Rodrigues de; Coelho, Luiz Fernando de Oliveira; Júnior, Eduardo Paulino; Pedrosa, Moisés Salgado (Seven Editora, 2023)
Fetal acardia is a rare complication that affects monochorionic/diaminiotic twin pregnancies and is characterized by the presence of a fetus with no heart (acardiac fetus) or a rudimentary heart (hemicardiac fetus). The objective of the present article is to present a case of fetal acardia with diagnosis confirmed by anatomopathological examination in which the "pump fetus" survived the pregnancy without specific treatment and without intercurrences. DOI:https://doi.org/10.56238/interdiinovationscrese-057